Cadiz debtors: the Constitution 1812 and education - Hernández Pina, Fuensanta; Escarbajal de Haro, Andrés; Monroy Hernández, Fuensanta (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
In this article, it is analyzed from the political history of education, the importance and influence that the Constitution of 1812 has had in education. This is one of the most important and transcendent legal documents in the history of Spain, at political, legislative, and social levels. Indeed, the Constitution of 1812 will go down in history as the first that devoted an entire section of its articles to education, with essential elements of renovation that will influence greatly the educational future of our country. These new elements are focused on the defense of universality of primary education for the entire population, without exceptions, and on uniformity of the curricula throughout the State. It must be remembered that in the XIX century, Spanish liberalism had a major obstacle for establishing a political system based on the sovereignty of the nation, equal rights, freedom, and the inclusion of citizens in political life: ignorant people, endemic illiteracy of Spain at that historical period. Therefore, and as it did before the Enlightenment, liberals sought to respond to this situation by promoting education and scientific knowledge as a basis for a new, modern nation. Thus, from primary sources and supported by educational legislation, it is concluded that the Spanish Liberals made a clear statement of intent by placing education not only as an important factor of progress but also as a basis for the new political regime that was being designed.